Islamic Religious Education Learning at Ma'had Islahuddin Wittaya, Yala, Southern Thailand - Muhammadsukree Waehama (Sufiya Journal of Islamic Studies, 2026)
This study aims to describe the implementation of Islamic Education learning at Ma’had Islahuddin Wittaya Yala, Southern Thailand. This research is motivated by the strategic position of Islamic educational institutions in Muslim-minority regions in preserving religious identity while simultaneously responding to the demands of educational modernization. This study employs a case study design. Data were gathered through in-depth interviews with the head of the ma'had, teachers, and students, supplemented by field observations and document analysis. Data analysis was carried out interactively through the sequential stages of data reduction, data display, and conclusion drawing. The findings indicate that the curriculum at Ma’had Islahuddin Wittaya Yala integrates Islamic sciences derived from classical Arabic literature with general subjects and skills development. The use of the Malay language as the medium of instruction in religious learning strengthens the ma'had's function as an educational institution as well as a means of preserving the cultural identity of the Patani community. Furthermore, the learning process is executed through systematic planning and the application of diverse methods—including lectures, discussions, demonstrations, experiments, storytelling, and field trips—which are tailored to the characteristics of the material and the needs of the students. The evaluation system combines formative and summative assessments through oral and written tests to comprehensively measure students' development across the cognitive, affective, and psychomotor domains. These findings confirm that the success of Islamic education in Muslim-minority regions is determined by the institution's capability to integrate Islamic values, the local socio-cultural context, and the demands of modern education. The implications of this study highlight the importance of contextual curriculum development, teacher capacity building, and the reinforcement of educational infrastructure to support the creation of an adaptive, inclusive, and sustainable Islamic learning system.